Faktor-Faktor yang Berpengaruh terhadap Kejadian Stunting Pada Balita Usia 24-59 Bulan yang Tinggal di Pesisir Pantai - Orisinal, Orisinal; Yasni, Hilma; Rasima, Rasima; Usrina, Nora; Raisah, Putri (Universitas Malahayati, 2025)
ABSTRACT Stunting is a growth failure that lasts for a long time when growing up with limited access to food and health services. Stunted children who come from families with clean water facilities have a 17% chance of achieving normal height when compared to stunted children who come from families who do not have clean water facilities. Stunting is a problem because it is associated with the risk of morbidity and death, brain development so that motor development is delayed. To determine the relationship between factors that influence the incidence of stunting in toddlers aged 24-59 months who live on the coast. The research method used was observational with a cross-sectional design. The population in this study were all toddlers who lived on the coast of the Susoh Community. The sample in the research was parents who had toddlers aged 24-59 months, with sample criteria in the research namely being willing to be respondents, toddlers aged 24-59 months, toddlers monitoring their body and development at the Posyandu, having a KIA book. The sampling technique was carried out using multistage sampling, namely cluster random sampling with a total sample in the study of 69 toddlers consisting of 4 villages in the Susoh Community Health Center area. The data collection method uses primary data and secondary data through interviews and observation. Data analysis in this research is univariate, bivariate and multivariate. The statistical test used is logistic regression with a confidence level of 95% which is analyzed with STATA software. There is no relationship between the factors clean water sources, access to clean water, clean water quality, latrines, employment, and income with the incidence of stunting in children under five (p>0.05). There is a relationship between sanitation factors, waste management, education level and the incidence of stunting in toddlers (p<0.05). There is no relationship between clean water sources, access to clean water, clean water quality, latrines, employment and income and the incidence of stunting in children under five. There is a relationship between sanitation factors, waste management, education level and the incidence of stunting in toddlers aged 24-59 months who live on the coast in the Susoh Community Health Center Working Area. Keywords: Stunting, Toddlers, Coastal Areas, Socio-Economics, Water Resources, Sanitation ABSTRAK Stunting merupakan kegagalan pertumbuhan yang berlangsung dalam jangka waktu lama ketika tumbuh dengan keterbatasan akses terhadap makanan dan pelayanan kesehatan. Balita stunting berawal dari keluarga dengan fasilitas air bersih memiliki kesempatan sebesar 17% untuk mencapai tinggi badan normal bila dibandingkan dengan anak stunting yang berasal dari keluarga yang tidak memiliki fasilitas air bersih. Stunting menjadi permasalahan karena berhubungan dengan risiko kesakitan dan kematian, perkembangan otak sehingga perkembanagan motorik terlabat. Tujuan Penelitian untuk mengetahui hubungan faktor-faktor yang berpengaruh terhadap kejadian stunting pada balita usia 24-59 bulan yang tinggal di pesisir pantai. Metode penelitian yang digunakan observasional dengan rancangan crossectional. Populasi dalam penelitian ini adalah adalah seluruh balita yang tinggal di pesisir pantai. Sampel dalam penelitian orang tua yang mempunyai balita usia 24-59 bulan, dengan kriteria sampel dalam penelitian yaitu bersedia menjadi responden, balita berusia 24-59 bulan, balita melakukan pemantau tubuh kembang di Posyandu, memiliki buku KIA. Teknik pengambilan sampel dilakukan secara multistage sampling yaitu cluster random sampling dengan jumlah sampel dalam penelitian 69 balita yang terdiri dari 4 desa yang ada diwilayah Puskesmas Susoh. Metode pengumpulan data menggunakan data primer dan data sekunder melalui wawancara dan observasi. Analisa data dalam penelitian ini berupa univariat, bivariat, dan multivariat. Uji statistic yang digunakan yaitu regresi logistik dengan tingkat kepercayaan 95% yang di analisa dengan Software STATA. Tidak ada hubungan antara faktor sumber air bersih, akses air bersih, kualitas air bersih, jamban, pekerjaan, dan penghasilan dengan kejadian stunting pada balita (p>0.05). Ada hubungan antara faktor sanitasi, pengelolaan limbah, tingkat pendidikan dengan kejadian stunting pada balita (p<0.05). Tidak ada hubungan antara faktor sumber air bersih, akses air bersih, kualitas air bersih, jamban, pekerjaan, dan penghasilan dengan kejadian stunting pada balita. Ada hubungan antara faktor sanitasi, pengelolaan limbah, tingkat pendidikan dengan kejadian stunting pada balita usia 24-59 bulan yang tinggal di pesisir pantai di Wilayah Kerja Puskemas Susoh Kata Kunci: Stunting, Balita, Pesisir Pantai, Sosial Ekonomi, Sumber Air, Sanitasi